Deformation and fracture of sandwich concrete structures reinforced with carbon fiber under shock-wave loading - Belov, Nikolai N.; Plyaskin, Andrey S.; Yugov, Nikolai T.; Potekaev, Aleksandr I. 1951-; Klopotov, Anatoly A.; Yugov, A. A.; Useinov, E. S.; Bunkov, Victor E. (Russian physics journal)
The processes of deformation and fracture of sandwich structures on the front and rear sides of concrete slabs are investigated under shock-wave loading. A model is proposed, which describes these processes in terms of continuum mechanics. The influence of the front and rear layers of a fine-grained concrete barrier reinforced with carbon fiber on the penetration of a steel indenter is studied in the range of impact velocities between 1000-1500 m/s. It is found out that 120% more energy has to be spent in order to break through this reinforced barrier from either side compared to the non-reinforced case.